Regional prevalence and determinants of exclusive breastfeeding in India - Felix Akpojene Ogbo; Mansi Vijaybhai Dhami; Akorede O. Awosemo; Bolajoko O. Olusanya; Jacob Olusanya; Uchechukwu L. Osuagwu; Pramesh Raj Ghimire; Andrew Page; Kingsley E. Agho (BMC, 2019)
Abstract Background Exclusive breastfeeding (EBF) has important benefits for both the mother and child. In India, no nationwide studies have examined patterns of EBF in the past decade to inform national and subnational breastfeeding programmes. The present study aimed to investigate the regional prevalence and determinants of EBF in India. Methods This study used a total weighted sample of 21,352 from the 2015-2016 India National Family Health Survey. EBF was measured as the proportion of infants 0-5 months of age who received breast milk as the only source of nourishment, based on mother's recall on feeds given to the infant 24 h before the survey. The prevalence of EBF and other breastfeeding patterns were estimated by region, and multivariable logistic regression that adjusted for clustering and sampling weights was used to investigate the association between the study factors (child, maternal, household, health service and community factors) and EBF by regional areas in India. Results This study indicated that wide differences in the prevalence of EBF and other childhood feeding practices exist across regions of India, where Southern India had the highest EBF prevalence (79.2%) and the North-East reported the lowest (68.0%). EBF prevalence decreased with infant age, dropping faster in the South (43.7% at 5 months) compared to the North-East region (54.0% at 5 months). Similarly, substantial variations in key determinants of EBF were evident by region, where higher birth order was the only common factor associated with non-EBF across all regions. Key modifiable determinants of non-EBF included higher maternal education in the South and belonging to rich households in Central India, while those for EBF were higher maternal education in the Central region and frequent antenatal care (≥ 4) visits in Northern India. Conclusion This study demonstrates wide variations in regional prevalence and determinants of EBF in India. Improving EBF participation in India would require multifaceted national and subnational efforts that include dedicated funds and the establishment of appropriate policy and interventions that are consistently monitored and evaluated.